Protective Effect of Botulinum Toxin against Ultraviolet-Induced Skin Pigmentation. Issue 2 (August 2019) - Jung, Jae-A; Kim, Beom-Jun; Kim, Min-Sook; You, Hi-Jin; Yoon, Eul-Sik; Dhong, Eun-Sang; Park, Seung-Ha; Kim, Deok-Woo
Abstract : Background: Hyperpigmentation following ultraviolet irradiation has cosmetic concerns. Botulinum toxin type A can favorably affect skin pigmentation. However, the mechanism of skin pigmentation is unclear. Methods: In vitro, human epidermal melanocytes were co-cultured with human keratinocytes. After cells were treated with botulinum toxin type A, cell morphology, proliferation, and dendricity were analyzed, and immunofluorescence, tyrosinase activity, and melanin contents were determined. To evaluate the effect of botulinum toxin type A on ultraviolet B–irradiated mouse skin, ultraviolet B alone was applied to one side of the back of each mouse as a control, whereas ultraviolet B plus injection of botulinum toxin type A was applied to the contralateral side. Skin pigmentation, histology, and the number of dihydroxyphenylalanine-positive melanocytes were evaluated. The L * colorimeter value was measured. Enzyme-linked immunosorbent assay determinations of basic fibroblast growth factor, interleukin-1 alpha, and prostaglandin E2 were performed. Results: Immunohistochemical staining revealed botulinum toxin type A in the cytoplasm of melanocytes and in the positive control. In vitro, melanocyte dendricity and melanin contents were decreased slightly but significantly ( p < 0.05) after botulinum toxin type A treatment. In vivo, botulinum toxin type A suppressed skin pigmentation. The number of dihydroxyphenylalanine-positive melanocytes was also significantly lower than in the control side. Tyrosinase activity and melanin content were also significantly reduced ( p < 0.05). Botulinum toxin type A also significantly reduced the amounts of basic fibroblast growth factor, interleukin-1 alpha, and prostaglandin E2 (all p < 0.05). Conclusion: Botulinum toxin type A can suppress epidermal melanogenesis through both direct and indirect mechanisms.